Ecological and Human Health Implications of Heavy Metal Pollution in Nigerian Artisanal Mining Communities: A Meta-Analytical Review (2010-2024) - Odetunde, Simeon Kolawole; Yusuf, Afeez Olabisi; Sunmon, Omodolapo; Oladetuyi, Adedayo Peter; Godspower, Oghale Ijeoma (Journal of Sustainability and Environmental Management, 2025)
Mining activities across Nigeria have led to significant contamination of soils with heavy metals, posing serious ecological and public health concerns. The extent of contamination and associated health risks vary by region and metal type, necessitating a systematic synthesis of available data. This study aimed to systematically review and quantitatively analyze heavy metal contamination and human health risk assessments in soils from five key mining regions in Nigeria, covering multiple geo-political zones. A systematic review and meta-analysis were conducted following PRISMA 2020 guidelines. A comprehensive search of peer-reviewed articles, theses, and technical reports (2010–2024) was performed across multiple databases and grey literature sources. Eligible studies reported soil concentrations of heavy metals (e.g., Pb, Cd, Zn, Cu, Ni) and associated health risk metrics such as hazard quotients (HQ), hazard index (HI), and carcinogenic risks (CR). Data from 40 studies were included in the qualitative synthesis, with 30 eligible for meta-analysis. Standard contamination indices (CF, EF, I_geo, PLI, PERI) and U.S. EPA risk models were applied. Data were analyzed using fixed- or random-effects meta-analytical models, and heterogeneity was assessed using I² statistics. The highest contamination levels were observed in soils from Zamfara and Enyigba, with lead (Pb) and cadmium (Cd) frequently exceeding WHO/FAO safe limits. Meta-analytical estimates of non-carcinogenic risk (HI > 1) and carcinogenic risk (CR > 1E-04) were particularly elevated in children, indicating significant health hazards. Pollution indices confirmed widespread enrichment and ecological threat across study areas. Multivariate analyses suggested common anthropogenic sources, with strong correlations between Pb, Zn, and Cd. The methodological consistency enabled robust site-wise comparisons and risk stratification. Heavy metal pollution in Nigerian mining zones is widespread and poses substantial ecological and public health risks, especially in artisanal and small-scale mining communities. Targeted mitigation measures, policy interventions, and continuous environmental monitoring are urgently required. This study provides critical baseline data for regulatory frameworks and future risk management strategies.